The Urgency Of Providing Restitution As Legal Protection For Victims Of Criminal Acts Implementing Article 178 Of Law No. 20 Of 2025 Concerning The Criminal Procedure Code - Edy Sugiarto (Siber International Journal of Advanced Law (SIJAL), 2026)
Development law modern criminal law begins shift from paradigm orientation offender-oriented towards victim-oriented research This motivated by frequent neglected recovery victim's rights in system justice classic, where the victim tends to only become witness passive. Research objectives This is analyze construction normative giving restitution in Article 178 of Law No. 20 of 2025 concerning the Criminal Procedure Code as well as formulate a renewal model criminal procedure law For optimize right The research method used is juridical normative with approach legislation and conceptual. Research results show that Article 178 of the 2025 Criminal Procedure Code strengthens the victim's position with integrate restitution to in the judicial process criminal, giving strength executive, and expanding role apparatus enforcer law. However, its implementation Still hampered by factors administrative and capabilities economy perpetrators. In conclusion, strengthening protection law for victims requires a comprehensive reform model, including integration restitution in every stage justice, implementation justice restorative, formation institution manager restitution special, and utilization technology information to ensure justice substantive for the victims.